Pengaruh Penggunaan Video Digital terhadap Hasil Belajar Teknik Dasar Bola Voli pada Siswa SD Negeri 1 Semondo - Indra Sudrajat; Jaka Sayyidina Ali (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aimed to determine the effect of using digital video on learning outcomes of basic volleyball techniques among students at SD Negeri 1 Semondo. The study employed a quantitative approach using an experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 17 fifth-grade students selected through purposive sampling. The research instrument was a volleyball skills battery test covering underhand service, forearm passing, overhead passing, smash, and block. Data were collected through pretest, treatment using digital video-based learning media, and posttest. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Paired Sample t-test at a significance level of 5%. The findings revealed that students' average learning outcomes improved after the implementation of digital video-based learning. The hypothesis testing showed a significance value (Sig. 2-tailed) of less than 0.05, indicating a significant difference between the pretest and posttest scores. Therefore, the use of digital video had a significant positive effect on improving students' learning outcomes in basic volleyball techniques at SD Negeri 1 Semondo. Digital video learning media helped students understand movement techniques more clearly, increased their learning motivation, and made the physical education learning process more effective and engaging.